FROM THE EDITORS - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2013)
The disparity between strategic aspirations and affordable resources is a strategic reality confronting all militaries. Strategic aspirations tend to be international and foreign policy in orientation, whilst resource decisions are made in the context of the domestic political domain. Both these decision environments or realities may severely affect military forces as was dramatically illustrated recently by the military episode in the Central African Republic. The ordeal, in which fifteen South African servicemen were killed, not only brought South Africa’s strategic aspirations in the spotlight; it also highlighted a range of perceived South African political, military and operational deficiencies. Some consider this to be South Africa’s Srebrenicamoment and an opportunity for military strategic, operational and institutional introspection.